Understanding Motor Skills in Children with Dyspraxia, ADHD, Autism, and Other Learning Disabilities : a Guide to Improving Coordination. - Kurtz, Lisa A. (JKP essentials., 2007)
'The book is user-friendly and includes clear diagrams in each section, along with tables to outline key points. I found these very useful and they are an easy reference/ reminder, for example, they include a normal development chart, what assessments are available and their main aims.'. - National Association of Paediatric Occupational Therapists. Children with learning disabilities often have coordination problems that make everyday activities such as mealtimes, dressing, playing sports, and learning to write challenging. This accessible manual for parents and professionals offers advice on.